Metode Pembinaan Akhlak Berpakaian Oleh Guru Pendidikan Agama Islam di SMPN 1 Mandah Kecamatan Mandah Provinsi Riau - Nirwana Putri; Wedra Aprison (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This study is motivated by the results of a problem found by several researchers, namely that there are some students who wear a headscarf but do not cover their breasts so that the body shape is visible, and there are also students who do not cover their genitals completely. Therefore, the teacher uses several methods to promote dress etiquette. The purpose of this study was to describe the method used by Islamic religious education teachers to promote clothing style in SMPN 1 Mandah, Mandah Regency, Riau Province. The type of research used in this study is descriptive qualitative research. The informants consisted of key informants and support informants, students and auxiliary informants, ie. Muslim religious education teachers. When gathering information through interviews, observations, and documentation. Data analysis with data reduction, data presentation and conclusion. Test the validity of the material with source triangulation, ie. comparing the results of interviews with key informants and supporting informants with the results of the author's direct observation. The results of this study are summarized as follows: that the teachers in SMPN 1 Mandah, Mandah Regency, Riau Province use several methods to promote the morals of students in dressing, namely: exemplary method, habit method, advisory method and punishment method.